Allocation to Anchor Investors, Underpricing, and the After‐Market Performance of IPOs. Issue 1 (9th May 2018) - Seth, Rama; Vishwanatha, S. R.; Prasad, Durga
Abstract: We study bidding by anchor investors in a two‐stage initial public offering (IPO) process and document a negative, causal relation between allocation to anchor investors and underpricing. We find that anchor investors are likely to invest in hard‐to‐place offerings characterized by valuation uncertainty. We also document a positive relation between allocation to reputed anchor investors and returns up to lock‐up expiration. Our evidence provides support for information revelation and targeting specific investors' theories of book building. Anchor‐backed IPOs earn superior returns mainly due to monitoring. Who bids in an IPO seems to matter just as particular types of bids do.